THE APPLICATION OF THE DEVELOPMENT OF CUSTOMARY INHERITANCE LAW ACCORDING TO THE JURISPRUDENCE OF THE SUPREME COURT - Ellyne Dwi Poespasari; Sri Hajati; S Soelistyowati (Fakultas Hukum Universitas Gadjah Mada, 2017)
AbstractCustomary inheritance law is influenced by the three kinship system. The Indonesian indigenous peoples, if there is a dispute about inheritance customs, completed the family council, if the hearts of deliberation families not bring results, then the Settlement shown to the Indigenous Institute, but when hearts division of inheritance still feel less satisfied BY Decision Traditional Leader Then Settlement of inheritance can be resolved in the court. Application of norms The jurisprudence of the Supreme Court Third hearts kinship system can be implemented yet, due to lack of knowledge of indigenous peoples against jurisprudence. Jurisprudence singer known only hearts Verdict The heritage dispute resolved by the Court InstituteIntisariHukum waris adat masih dipengaruhi tiga sistem kekerabatan Pada masyarakat adat jika terjadi sengketa waris adat, diselesaikan musyawarah keluarga, apabila dalam musyawarah keluarga tidak membawa hasil, maka penyelesaian kepada lembaga adat, namun apabila dalam pembagian harta waris masih merasa kurang puas dengan putusan ketua adat maka penyelesaian waris dapat diselesaikan di pengadilan. Penerapan norma Yurisprudensi Mahkamah Agung dalam ketiga sistem kekerabatan belum dapat dilaksanakan, disebabkan kurangnya pengetahuan masyarakat adat terhadap yurisprudensi. Yurisprudensi ini hanya dikenal dalam putusan sengketa warisan yang diselesaikan oleh lembaga pengadilan.